What is known about adolescent dysmenorrhoea in (and for) community health settings? - Dixon, Sharon; Hirst, Jennifer; Taghinejadi, Neda; Duddy, Claire; Vincent, Katy; Ziebland, Sue (Frontiers in Reproductive Health, 2024)
Introduction Dysmenorrhoea affects many adolescents with significant impacts on education and well-being. In the UK, most of the adolescents who seek care (and many never do), will do so through general practice (primary care). Knowing how best to care for adolescents reporting menstrual pain is an area where UK general practitioners would like better guidance and resources. Methods This mixed-methods narrative synthesis collates community and specialist evidence from 320 papers about adolescent dysmenorrhoea, with a UK general practice community health perspective. Results We report a narrative summary of symptoms, cause, consequences and treatments for adolescent dysmenorrhoea. We highlight areas of tension or conflicted evidence relevant to primary care alongside areas of uncertainty and research gaps identified through this synthesis with input from lived experience advisers Discussion There is little evidence about primary care management of adolescent dysmenorrhoea or specific resources to support shared-decision making in general practice, although there are evidence-based treatments to offer. Primary care encounters also represent potential opportunities to consider whether the possibility of underlying or associated health conditions contributing to symptoms of dysmenorrhoea, but there is little epidemiological evidence about prevalence from within community health settings to inform this. The areas where there is little or uncertain evidence along the care journey for adolescent dysmenorrhoea, including at the interface between experience and expression of symptoms and potential underlying contributory causes warrant further exploration. Systematic Review Registration https://www.crd.york.ac.uk/PROSPEROFILES/256458_STRATEGY_20210608.pdf, identifier (CRD42021256458).